Pengaruh Kualitas Pelayanan dan Fasilitas terhadap Kepuasan Pengunjung Booth Lokapala pada Event 14th Iesf World E-Sport Cup di Merusaka Hotel Bali - Harahap, Muhammad Iqbal Fauzi; Pasaribu, Ika Mary (Universitas Pahlawan Tuanku Tambusai, 2024)
E-sports (electronic sport) is a form of sports competition that uses video games. E-sports have become very popular and attract millions of viewers through online streaming. The 14TH IESF World E-Sport Cup is an e-sport world cup event. Lokapala was present as one of the booth exhibition fillers to showcase and introduce games made by the nation's children to visitors to the 14TH IESF World E-Sport Cup Event at Merusaka Hotel Bali. The Lokapala booth provides services and facilities for visitors who come. Research was conducted to determine the quality of service and facilities to the satisfaction of Lokapala booth visitors. Data processing analysis was carried out using the SPSS 25 program by conducting validity tests, reliability tests, normality tests, multicollinearity tests, heteroscedasticity tests, multiple linear regression tests, significance tests (t tests and F tests), and the coefficient of determination. The results in this study indicate that service quality and facilities have a positive and significant effect on visitor satisfaction.